2019
DOI: 10.1016/j.jmbbm.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Exposure effects of endotoxin-free titanium-based wear particles to human osteoblasts

Abstract: Titanium-based materials are widely employed by the biomedical industry in orthopedic and dental implants. However, when placed into the human body, these materials are highly susceptible to degradation processes, such as corrosion, wear, and tribocorrosion. As a consequence, metallic ions or particles (debris) may be released, and although several studies have been conducted in recent years to better understand the effects of their exposure to living cells, a consensual opinion has not yet been obtained. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Aseptic mobilization, one of the main issues contributing to failure of endoprostheses, depends also on the fine biological system regulating osteosynthesis and osteolysis, 54 , 55 which in turn could be affected by a possible inflammatory response induced by free nanoparticles or material debris. 56 SLM technique, in fact, produces irregular surfaces due to resolution allowed by the laser spot diameter with respect to the powder size. Although the main cellular inflammatory response can be generated by the presence of few μm sized debris, 57 the possible presence of unmelted CoCr powder could warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Aseptic mobilization, one of the main issues contributing to failure of endoprostheses, depends also on the fine biological system regulating osteosynthesis and osteolysis, 54 , 55 which in turn could be affected by a possible inflammatory response induced by free nanoparticles or material debris. 56 SLM technique, in fact, produces irregular surfaces due to resolution allowed by the laser spot diameter with respect to the powder size. Although the main cellular inflammatory response can be generated by the presence of few μm sized debris, 57 the possible presence of unmelted CoCr powder could warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between excessive ROS generation and an insufficient anti-oxidant defense mechanism reduces boneimplant osseointegration, further inducing aseptic loosening. Thus, there is a need for biomaterials with bioactive surface coating with anti-oxidant properties to improve implant osteointegration, stability, thus improving the effective lifespan [87]. Several anti-oxidant strategies have been explored to reduce ROS formation in different prosthetic biomaterials, ranging from surface functionalization to material doping with anti-oxidant agents, according to the different implant biomaterial, as well as nutritional supplementation.…”
Section: Anti-oxidant Strategy To Prevent Implant Failurementioning
confidence: 99%
“…Indeed, titanium biomaterials may induce an innate/adaptive immune: in particular, this material induces the production of pro-inflammatory cytokines and enhance free radical generation in the periosteum covering titanium implant [89]. In titanium (Ti) substrates, in order to improve the anti-oxidant activity for enhanced bone formation, multilayered structure composing of chitosan-catechol (chi-C), gelatin (gel), and hydroxyapatite (HA) nanofibers was added, resulting in a significative increase of implant osteointegration, and promotes osteogenesis under conditions of oxidative stress [87]. An emerging anti-oxidant agent against titanium particles induced aseptic loosening is resveratrol.…”
Section: Anti-oxidant Strategy To Prevent Implant Failurementioning
confidence: 99%
“…In contact with biological fluids, the free Ti, and metal-like particles can dissolve and generate ions that are accumulated in peri-implant bone (He et al, 2016) or migrate systemically to several organs of the body (Meyer et al, 2006). Some studies reported that Ti wear particles have different sizes and morphologies, from round to elongated, and ranging from 1 to 54 µm that can affect the surrounding living cells and tissues (Suárez-López Del Amo et al, 2018;Costa et al, 2019). Therefore, these Ti products are mainly associated with aseptic loosening of the orthopedics implants (Meyer et al, 2006) and pathogenesis of peri-implantitis through various mechanisms (Fretwurst et al, 2016;Safioti et al, 2017).…”
Section: Do Bio-tribocorrosion Products Affect the Peri-implant Tissumentioning
confidence: 99%